High Nitrogen Supply Induces Physiological Responsiveness to Long Photoperiod in Barley - Zeng, Jian (Front Plant Sci, 2017)
Photoperiod and nutrient nitrogen (N) supply influence the growth, development, and productivity of crops. This study examined the physiological, biochemical, and morpho-anatomical traits of NA5 and NA9, two barley cultivars with contrasting photoperiod lengths, under the combined treatment of photoperiod regime and N supply. Under long photoperiod, high N supply decreased net photosynthesis; decreased chlorophyll a and chlorophyll a/b; decreased ascorbate peroxidase (APX), catalase (CAT), and superoxide dismutase (SOD) activities; decreased ascorbate, glutathione, soluble protein, and soluble sugar; destroyed mesophyll cell integrity; and increased [Formula: see text] , malondialdehyde, and proline in both NA5 and NA9. Under short photoperiod, high N content increased net photosynthesis; increased chlorophyll a and chlorophyll a/b; increased APX, CAT, and SOD activities; and increased antioxidants, soluble protein, and soluble sugar in NA9 but decreased the same parameters in NA5. These results indicated that N supply strongly affected photosynthetic capacity and the balance of reactive oxygen species in response to short and long photoperiod. High N supply enhanced the sensitivity of long-day barley to photoperiod change by inhibiting photosynthesis and decreasing antioxidant defense ability. High N mitigated the undesirable effects of shortened photoperiod in short-day barley. Therefore, the data from this study revealed that N status affects adaptation to photoperiod changes by maintaining redox homeostasis and photosynthetic capacity.